متشابه الصفات واختلاف العلماء فيه - عبيد، أحمد إمام عبدالعزيز (جامعة الأزهر - كلية الدراسات الإسلامية والعربية للبنات بكفر الشيخ, 2022)
يتناول هذا البحث موضوعا هاما من موضوعات علوم القرآن وهو متشابه الصفات الذي يتفرع من المحكم والمتشابه وقد تناولت الحديث فيه أولا عن تعريف المحكم والمتشابه وبيان المراد بمتشابه الصفات والفرق بين متشابه الصفات وغيره من الصفات الأخرى، ثم تحدثت عن مذهب أهل السنة والجماعة في متشابه الصفات، وبينت أقوالهم الثلاثة في هذا الموضوع (التفويض والتأويل والتوسط بين التفويض والتأويل)، ثم خلصت إلى رجحان الأقوال الثلاثة لأهل السنة والجماعة جميعها، وأن من يعتقد أحدها لا ينكر عليه، ثم بينت مذهب بعض الفرق الأخرى في متشابه الصفات، مثل المشبهة والمجسمة، وبينت ضلال هذه الفرقة وبعدها عن الجادة والصواب، ثم بينت مذهب الإمام ابن تيمية في متشابه الصفات (الإثبات مع عدم التشبيه والتمثيل) وبينت خطأه -رحمه الله تعالى- في هذه القضية، وأنه قد جانبه الصواب، لكن خطأه أقل وطأة وأخف ضررا من المشبهة والمجسمة، ثم ذكرت نماذج من بعض الآيات القرآنية التي تتحدث عن متشابه الصفات، وهي قوله تعالى ﴿الرَّحْمَنُ عَلَى الْعَرْشِ اسْتَوَى﴾ (طه: ٥)، وقوله تعالى ﴿يَدُ اللَّهِ فَوْقَ أَيْدِيهِمْ﴾ (الفتح: ۱۰)، وقوله تعالى ﴿كُلُّ مَنْ عَلَيْهَا فَانٍ (26) وَيَبْقَى وَجْهُ رَبِّكَ ذُو الْجَلَالِ وَالْإِكْرَامِ﴾ (الرحمن: ٢٦- ۲۷)، وقمت بتفسيرها ودراستها وبيان أقوال المفسرين والعلماء فيها. وقد توصلت إلى بعض النتائج، منها: 1- أن مذهب أهل السنة والجماعة بآرائه الثلاثة في متشابه الصفات هو الصواب والأسلم، وعلى المسلم أن يختار منها ما شاء، ولا ينكر على من اتبع أحدها. 2- من الممكن أن يرجح رأي من الآراء الثلاثة لأهل السنة والجماعة في بعض الآيات، ويرجح آخر في آيات أخرى. 3- في بعض الآيات يكون الغرض الأساسي من الآية شيء آخر غير ما اختلف فيه العلماء، حيث يكون ذكره عرضا وليس أساسا في الآية. This research treat a very important subject of the Quran Sciences. It is The confusing attributes of Allah which is a branch of The controlled and confusing attributes of Allah. I began treating it first by identification of The controlled and confusing attributes of Allah, clarifying what is meant by The confusing attributes of Allah, and the difference between The confusing attributes of Allah and other attributes of Allah. Then I showed the position of the people of Sunna and Community in The confusing attributes of Allah, pointing to their three opinions in this subject (Tafweed, Taaweel and the medium between Tafweed and Taaweel). I came to a conclusion that all the three opinions of the people of Sunna and Community are preferable, and any person adopts one of them is not to be blamed. Then I showed the position of other sects in The confusing attributes of Allah like Al-mushabehah and Al- Mugassimah, and affirmed their delusion and deviation from the truth. After that I showed the position of Ibn – Taymyiah concerning the confusing attributes of Allah(the confirmation of the confusing attributes of Allah with negation of similarity and formation, and showed his error (Let Allah grant him mercy), and that he was deviated from truth, but his error is less harmful than Al-Mushabehah and Al-Mugassimah. Then I mentioned examples of some Quranic ayat Which treat The confusing attributes of Allah such as: (The All-Merciful was settled on the Throne) (The hand of Allah is over their hand) and (still existed the Face of Allah, the owner of Majesty and Generosity). I have explained and studied these ayats and mentioned the opinions of scholars about them. I have concluded these results: 1 – The position of the people of Sunna and Community with its three opinions is confident and truthful, and any Muslim can choice any of them without any rejection. 2 – One can prefer one of these three opinions of the people of Sunna and Community in some ayat, while another one can prefer another opinion in other ayat. 3- The essential goal in some ayat is another thing than what the scholars differentiate about it, as its mention is by chance and not essential in the ayat.
Keywords: القرآن الكريم -- متشابه الصفات -- أهل السنة -- الصفات الخبرية -- علوم القرآن